MODERN OPPORTUNITIES FOR ENHANCING CREATIVITY IN PRIMARY STUDENTS - Abdiyeva , Koysintosh; Jovliyeva , Dilshoda (INTERNATIONAL CONFERENCE ON SCIENCE, INNOVATION AND GLOBAL DEVELOPMENT, 2026)
This article broadly covers the essence of the concept of creativity, its role in the development of the individual and society, as well as the possibilities of increasing creativity based on modern technologies and innovative approaches. The importance of digital tools, educational technologies, artificial intelligence and interactive methods in the formation of creative thinking is analyzed on a scientific basis.